The impact of ergonomic practices on housekeeping employee retention and efficiency in hotels during COVID-19 in India - Singh, Amrik; Singh, Vipin Kumar (Turyzm/Tourism, 2022)
This article explores the current status of housekeeping-employee retention and efficiency in hotels particularly during COVID-19 in India, then discusses the implications of ergonomic practices on these. Ergonomic practice research in hotel housekeeping has been given enlarged scholarly attention, yet similar research in the Indian context is almost non-existent. Housekeeping work involves considerable physical effort that can lead to discomfort or even injury. This research involved 210 housekeeping employees from five-star hotels through an online survey. The data were interpreted using the partial least square (PLS) software SmartPLS 2.0. The constructs used in the study were working conditions, risk assessment and control, pandemic response plan, employee efficiency and employee retention. Working conditions were found to have a significant positive relationship with employee retention, whereas, risk assessment and control was found to have a positive relationship with employee retention and employee efficiency. Also, the pandemic response plan was found to have a positive relationship with employee efficiency. The pandemic response plan was not found to have a significant positive relationship with employee retention, while working conditions were not found to have a significant positive relationship with employee efficiency either.